Do Aligned Bodies Align Minds? The Partners' Body Alignment as a Constraint on Spatial Perspective Use. Issue 2 (7th February 2020) - Galati, Alexia; Symeonidou, Angela; Avraamides, Marios N.
ABSTRACT: In a direction-giving task, we examine whether a high-level constraint—the task partners' relative body alignment—influences spatial language use and task accuracy. In 32 pairs, task partners interacted in two conditions: for one route description, direction givers (DGs) and direction followers (DFs) sat side-by-side ( aligned condition), and for another they sat opposite one another ( counter-aligned condition). After each description, DFs drew the route on a map. When pairs were counter-aligned (vs. aligned), DGs increased their use of expressions from a survey perspective, using more frequently terms such as east-west . When counter-aligned, DFs also used more words per conversational turn, which was taken to reflect the increased difficulty of coordinating in that condition. Still, in terms of task performance, the accuracy of DFs' drawings was unaffected by the partners' body alignment or spatial language use; it was only predicted by the DGs' spatial ability. We argue that, because direction giving emphasizes accuracy, task partners invest in strategies that contribute to mutual understanding (e.g., recaps of the route by the DF at the end, evidenced by shifts in language use over time). Thus, body alignment in direction giving impacts coordination difficulty and spatial language use, but it does not singularly influence task performance.